CXCL4-induced PBMCs modulate vascular extracellular matrix via Wnt5a-dependent matrix metalloproteinase-7 and calcifying extracellular vesicle release - Krohn, Jona B.; Sprehe, Laurine Kristin; Sicklinger, Florian; Kawohl, Julie; Hess, Chiara; Spieler, Anja; Dihlmann, Susanne; Eis, Larissa; Gleißner, Christian A.; Katus, Hugo; Frey, Norbert; Leuschner, Florian (Arteriosclerosis, thrombosis, and vascular biology, 2025)
BACKGROUND: - The role of macrophage heterogeneity has become increasingly well-recognized in the study of vascular inflammatory responses. The CXCL4 (chemokine [C-X-C motif] ligand 4)-induced monocyte/macrophage phenotype has been implicated in atherosclerotic plaque destabilization, a key process preceding plaque rupture. Monocyte-derived macrophages differentiated with CXCL4 exhibit a unique transcriptome characterized by upregulation of S100A8 (S100 calcium-binding protein A8/calgranulin A) and MMP7 (matrix metalloproteinase-7). However, the mechanisms involved in CXCL4-induced monocyte-mediated vascular inflammation are unknown. - METHODS: - Single-cell RNA sequencing data were examined for CXCL4-dependent transcriptional signatures in plaque macrophages. Human peripheral blood-derived monocytes (PBMCs) differentiated with CXCL4 were characterized in terms of osteogenic signatures and calcifying extracellular vesicle (EV) release. Association of the CXCL4-induced phenotype with the Wnt (wingless-type) pathway was investigated, and CXCL4-induced PBMC-derived EV were analyzed for their calcification potential in ECM (extracellular matrix) hydrogels and their ability to elicit an inflammatory response in vascular smooth muscle cells. In vitro findings were verified histologically in human carotid artery plaques. - RESULTS: - In human plaque macrophages, single-cell sequencing revealed a CXCL4-susceptible subpopulation bearing a distinct proinflammatory transcriptional signature. CXCL4-differentiated PBMCs exhibited a marked induction of S100A8, MMP7, and osteogenic marker transcription concomitant with augmented release of calcifying EV enriched with MMP7, S100A8, Anx5 (annexin 5), and ALP (alkaline phosphatase). Under osteogenic conditions, PBMCs and their secreted EV independently increased the calcification of the ECM in vitro. Analysis of inflammatory pathway activation identified the Wnt5a-CaMKII (wingless-type 5a-calcium/calmodulin-dependent protein kinase II) signaling axis to be linked to the CXCL4-induced osteogenic PBMC phenotype, EV calcification potential, and enrichment with MMP7 and S100A8. In addition, CXCL4-polarized PBMC-derived EV stimulated inflammatory gene expression in vascular smooth muscle cells. In human carotid artery plaques, CXCL4-induced macrophage abundance coincided with Wnt5a-CaMKII pathway activation and progressive plaque calcification. - CONCLUSIONS: - This study introduces a novel mechanism driving monocyte-mediated ECM remodeling in procalcific inflammatory responses through Wnt5a-CaMKII-activated secretion of MMP7+S100A8+ calcifying EV by CXCL4-induced proinflammatory monocytes.